The mode of action of bone morphogenetic protein (bmp) in the regulation of ovarian function - Regan, Sheena Linnette Patricia (Curtin University, 2015)
The aim of this thesis was to establish the specific role of bone morphogenetic protein (BMP) in the regulation of ovulation rate, and the effect of ageing on receptor expression. Ovarian follicle depletion was associated with a reduction in receptor expression. Growth hormone co-treatment during IVF reversed some of the ageing effects. The results are significant and central to the development of a new clinical approach to improve human female fertility.